ANALISIS KELAYAKAN USAHATANI KOPI DI KABUPATEN ENDE (Kajian pada Desa Niowula dan Randhoria) - Imaculata Fatima (Agriculture Faculty of Flores University, 2018)
Worthiness analysis of farmer coffee in Ende. One of the plantation commodities that is the buffer of the national economy is coffee. Likewise in Ende District coffee is cultivated by smallholders and contributes quite well in meeting the income of the farmers. But the reality shows that many coffee farmers are not concentrated on coffee plants alone because of the many other businesses that they do so that coffee production in Ende Regency is not optimal. Considering that coffee has become a mainstay product in Ende Regency, this study aims to determine the level of coffee farming income and the factors that influence farmers' income and analyze the feasibility and usefulness of a coffee farm. The method used in this research is a descriptive method. The research location was determined by purposive sampling, based on the consideration that the area was a coffee-producing region in Ende Regency. Sampling area is Niowula and Randhoria Village as the largest coffee producer in Ende Regency. The population of farmers is all coffee farmers, with 20 respondents. Data collection is done by interview, questionnaire, observation, and documentation. Feasibility analysis was carried out by B / C ratio analysis. The results showed a B / C ratio of 8.4%, which meant that the coffee business was profitable and feasible to develop. Factors influencing coffee business in Ende Regency include education levels, gender participation, the age of the workforce and the age of coffee plants that are old and have not applied profitable technology. It is recommended to farmers to focus more on cultivating coffee plants by applying P3S, and intensive post-harvest processing